2020
DOI: 10.1037/amp0000585
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction is a risk factor for overeating and obesity.

Abstract: This article introduces the rapidly growing literature linking cognitive dysfunction to overeating and obesity. Though neural responses to food and food cues can predispose individuals to overeating, these processes are moderated by a series of cognitive factors. Deficits in attentional bias, delay discounting, and episodic memory have clear connections to overeating in both laboratory and real-world settings. New weight loss interventions target these deficits through strategies designed to either directly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 200 publications
(258 reference statements)
2
28
0
Order By: Relevance
“…Problems related to attention and self-regulation that affect the patient's capacity to plan, set agreements and delay gratification can create barriers in all forms of obesity treatment. 31 In line with other studies, we found elevated levels of binge eating and depressive symptoms in this group of adolescents with severe obesity. However, contrary to our hypothesis, we did not find more such problems in those rated positive for ADHD or ASD by their parents.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Problems related to attention and self-regulation that affect the patient's capacity to plan, set agreements and delay gratification can create barriers in all forms of obesity treatment. 31 In line with other studies, we found elevated levels of binge eating and depressive symptoms in this group of adolescents with severe obesity. However, contrary to our hypothesis, we did not find more such problems in those rated positive for ADHD or ASD by their parents.…”
Section: Discussionsupporting
confidence: 93%
“…Such problems can put strain on the family and negatively affect cooperation between parents and the adolescent, including in regard to weight‐related issues. Problems related to attention and self‐regulation that affect the patient's capacity to plan, set agreements and delay gratification can create barriers in all forms of obesity treatment 31 …”
Section: Discussionmentioning
confidence: 99%
“…15 There are a number of other factors in play; for example, older people with cognitive impairment may have difficulties in expressing their wishes and needs for eating, leading to weight loss, 33 or such a group of individuals may inadvertently overeat, leading to obesity. 34 Overall, evidence from existing studies 5,22 indicates that attention should be directed to patients with high 4AT scores to identify reversible underlying causes of delirium and other adverse outcomes, with a focus on early and appropriate nutrition support. Prospective studies have shown that oral nutritional supplements help reduce both the length of stay in the hospital by 2.3 days and early hospital readmission by 2.3%.…”
Section: Discussionmentioning
confidence: 99%
“…This exaggerated preference for smaller, immediate rewards over larger, delayed rewards has been linked to all stages of drug addiction from initiation of use to addiction severity and treatment outcome [ 17 19 ]. Steeper discounting is also predictive of other maladaptive behaviors, such as gambling, risky sex, and overeating [ 20 22 ], suggesting that it may represent a trans-disease process [ 23 ]. Multiple brain regions across several large-scale neural networks are implicated in delay discounting, likely involving recursive interactions across networks [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%